Inverter‐based low‐power delta–sigma modulator using correlated level shifting technique. Issue 25 (1st December 2017) - Zhang, H.; Tan, Z.; Nguyen, K.
Abstract : A low‐power delta–sigma modulator based on inverter operational‐transconductance amplifiers (OTAs) using correlated level shifting technique (CLS) is presented. The CLS technique boosts the DC gain of inverter‐based OTA from 42 to 79 dB and extends the linear output swing from 55 to 80% of the full scale. Simulation results show that design in 180 nm CMOS technology, the proposed second‐order delta–sigma modulator achieves a signal‐to‐quantisation‐noise ratio improvement of 10.4 dB compared to a conventional inverter‐based modulator implementing the identical loop filter with the same oversampling ratio.